Is Use of BMP-2 Associated with Tumor Growth and Osteoblastic Differentiation in Murine Models of Osteosarcoma?. Issue 12 (December 2020) - Kendal, Joseph K.; Singla, Arvind; Affan, Asmaa; Hildebrand, Kurt; Al-Ani, Abdullah; Ungrin, Mark; Mahoney, Douglas J.; Itani, Doha; Jirik, Frank R.; Monument, Michael J.
Abstract: Background: The putative benefit of rhBMP-2 is in the setting of limb reconstruction using structural allografts, whether it be allograft-prosthetic composites, osteoarticular allografts, or intercalary segmental grafts. There are also potential advantages in augmenting osseointegration of uncemented endoprosthetics and in reducing infection. Recombinant human BMP-2 might mitigate nonunion in structural allograft augmented osteosarcoma limb salvage surgery; however, its use is limited because of concerns about the prooncogenic effects of the agent. Questions/purposes: (1) To assess if BMP-2 signaling influences osteosarcoma cell line growth. (2) To characterize degree of osteosarcoma cell line osteoblastic differentiation in response to BMP-2. (3) To assess if BMP-2 signaling has a consistent effect on local or systemic tumor burden in various orthotopic murine models of osteosarcoma. Methods: In this study, 143b, SaOS-2 and DLM8-M1 osteosarcoma cell lines were transfected with BMP-2 cDNA controlled by a constitutive promoter (experimental) or an empty vector (control) using a PiggyBac transposon system. Cellular proliferation was assessed using a quantitative MTT colorimetric assay. Osteoblastic differentiation was compared between control and experimental cell lines using quantitative real-time polymerase chain reaction of the osteoblastic markers connective tissue growth factor, Runx-2, Osterix, alkaline phosphatase and osteocalcin. Experimental and control cell lines were injected into the proximal tibia of either NOD-SCID (143b and SaOS-2 xenograft model), or C3H (DLM8-M1 syngeneic model) mice. Local tumor burden was quantitatively assessed using tumor volume caliper measurements and bioluminescence, and qualitatively assessed using post-mortem ex vivo microCT. Lung metastasis was qualitatively assessed by the presence of bioluminescence, and incidence was confirmed using histology. rhBMP-2 soaked absorbable collagen sponges (experimental) and sterile-H2 O soaked absorbable collagen sponges (control) were implanted adjacent to 143b proximal tibial cell line injections to compare the effects of exogenous BMP-2 application with endogenous upregulation. Results: Constitutive expression of BMP-2 increased the in vitro proliferation of 143b cells (absorbance values 1.2 ± 0.1 versus 0.89 ± 0.1, mean difference 0.36 [95% CI 0.12 to 0.6]; p = 0.01), but had no effect on SaOS-2 and DLM8-M1 cell proliferation. In response to constitutive BMP-2 expression, 143b cells had no differences in osteoblastic differentiation, while DLM8-M1 cells downregulated the early marker connective tissue growth factor (mean ΔCt 0.2 ± 0.1 versus 0.6 ± 0.1; p = 0.002) and upregulated the early-mid range marker Runx-2 (mean ΔCt -0.8 ± 0.1 versus -1.1 ± 0.1; p = 0.002), and SaOS-2 cells upregulated the mid-range marker Osterix (mean ΔCt -2.1 ± 0.6 versus -3.9 ± 0.6; p = 0.002). Constitutive expression of BMP-2 resulted in greater 143b and DLM8-M1 local tumor volume (143b: 307.2 ± 106.8 mm 3 versus 1316 ± 387.4 mm 3, mean difference 1009 mm 3 [95% CI 674.5 to 1343]; p < 0.001, DLM8-M1 week four: 0 mm 3 versus 326.1 ± 72.8 mm 3, mean difference 326.1 mm 3 [95% CI 121.2 to 531]; p = 0.009), but modestly reduced local tumor growth in SaOS-2 (9.5 x 10 8 ± 8.3x10 8 photons/s versus 9.3 x 10 7 ± 1.5 x 10 8 photons/s, mean difference 8.6 x 10 8 photons/s [95% CI 5.1 x 10 8 to 1.2 x 10 9 ]; p < 0.001). Application of exogenous rhBMP-2 also increased 143b local tumor volume (495 ± 91.9 mm 3 versus 1335 ± 102.7 mm 3, mean difference 840.3 mm 3 [95% CI 671.7 to 1009]; p < 0.001). Incidence of lung metastases was not different between experimental or control groups for all experimental conditions. Conclusions: As demonstrated by others, ectopic BMP-2 signaling has unpredictable effects on local tumor proliferation in murine models of osteosarcoma and does not consistently result in osteosarcoma cell line differentiation. Further investigations into other methods of safe bone and soft tissue healing augmentation and the use of differentiation therapies is warranted. Clinical Relevance: Our results indicate that BMP-2 has the potential to stimulate the growth of osteosarcoma cells that are poorly responsive to BMP-2 mediated osteoblastic differentiation. As this differentiation potential is unpredictable in the clinical setting, BMP-2 may promote the growth of microscopic residual tumor burden after resection. Our study provides further support for the recommendation to avoid the use of BMP-2 after limb-salvage surgery in patients with osteosarcoma.